2013
DOI: 10.1073/pnas.1312778110
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, ecology, and the Cambrian radiation of animals

Abstract: The Proterozoic-Cambrian transition records the appearance of essentially all animal body plans (phyla), yet to date no single hypothesis adequately explains both the timing of the event and the evident increase in diversity and disparity. Ecological triggers focused on escalatory predator–prey “arms races” can explain the evolutionary pattern but not its timing, whereas environmental triggers, particularly ocean/atmosphere oxygenation, do the reverse. Using modern oxygen minimum zones as an analog for Protero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
239
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(249 citation statements)
references
References 51 publications
8
239
0
2
Order By: Relevance
“…Cloud, 1968;Runnegar, 1982). Experimental work has also shown that the oxygen levels necessary to support small, primitive metazoans such as sponges (Porifera) are far lower (Mills et al, 2014) than those required for large, active, and A c c e p t e d M a n u s c r i p t 7 ecologically-important animals such as carnivorous predators (Sperling et al, 2013b;Knoll and Sperling, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud, 1968;Runnegar, 1982). Experimental work has also shown that the oxygen levels necessary to support small, primitive metazoans such as sponges (Porifera) are far lower (Mills et al, 2014) than those required for large, active, and A c c e p t e d M a n u s c r i p t 7 ecologically-important animals such as carnivorous predators (Sperling et al, 2013b;Knoll and Sperling, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These environmental data also showed that although small animals may be present at very low O 2 concentrations, the ecological richness associated with the Cambrian biota (particularly carnivory) requires O 2 concentrations perhaps closer to 10% PAL ( Fig. 1) (11,12). Under the hypothesis that animal evolution and O 2 are inexorably linked, these physiological and ecological constraints make a set of predictions for the geological record-specifically, that stable atmospheric O 2 concentrations did not rise above 1% PAL until relatively late in the Proterozoic Eon.…”
mentioning
confidence: 66%
“…In places where sea-floor oxygen levels are a bit higher -about 0.5-3% of concentrations at the sea surface -animals are more abundant but their food webs remain limited: the animals still feed on microbes rather than on each other. But around somewhere between 3% and 10%, predators emerge and start to consume other animals 4 .…”
Section: Modern Mirrorsmentioning
confidence: 99%